Intake of Fat, Fiber, Sodium and Sleep Quality on the Incident of Hypertension in Pre-Elderly - Sina Dwi Rahayu; Natalia Desy Putriningtyas (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Hypertension is a disease when a person's blood pressure exceeds normal limits. Hypertension can be caused by controllable and uncontrollable factors. Consumption of foods low in fiber, high in fat and sodium is one of the causes factors that can be controlled. This research was to analyze the relationship between intake of fat, fiber, sodium and sleep quality to hypertension in the Central Magelang Health Center area. This case control study used purposive sampling technique with a minimum number of cases and controls for each group of 47 subjects. The inclusion criteria for case subjects were grade 1 and 2 hypertension patients aged 45-59 years and had taken hypertension medication for the last 6 months. The inclusion criteria for the control group were men or women aged 45-59 years who did not had hypertension. Data was obtained by interviews using the SQ-FFQ and PSQI questionnaires. Data was performed using univariate analysis, bivariate analysis with the Spearman test and multivariate analysis with a linear regression test. The results obtained were fat and fiber intake had significant relationship (p-value=0,000) and (p-value=0,014) to systolic blood pressure. Sodium intake and sleep quality had significant relationship (p-value=0,000) and (p-value=0,000) to systolic blood pressure and diastolic blood pressure (p-value=0,047) and (p-value=0,003). Fat and fiber intake were related to systolic blood pressure, and sodium intake and sleep quality were related to systolic and diastolic blood pressure in hypertensive patients.